Robotic Renal Surgery Benign and Cancer Surgery for the Kidneys and Ureters - Abaza, Ronney. (Springer US : Imprint: Springer, 2013)
Robotic Renal Surgery: Benign andCancer Surgery for the Kidneys and Ureters provides a comprehensive review of the role of and technical considerations regarding robotic surgery for conditions of the kidney and associated conditions of the upper urinary tract. In addition to serving as a reference regarding indications, preoperative and postoperative management, complications, and evidence-based outcomes, this text also serves as a practical guide for surgeons in how to perform the complete array of robotic kidney and upper tract surgery. Included are detailed descriptions of positioning, instrumentation, and surgical steps for the surgeon newly adopting robotic surgery or for those refining their techniques. All chapters are written by recognized and published experts in the various techniques, creating an authoritative text on the subject. Robotic Renal Surgery: Benign andCancer Surgery for the Kidneys and Ureters will be of great value to urologists, robotic surgeons, fellows in urologic oncology or endourology as well as urology residents in training and surgical nurses and other surgery team members involved in these procedures.